Prey Diversity of Common Leopard and Factors Affecting Human-Common Leopard Conflict in Community Forests of Arghakhanchi District Nepal - Kunwar, Ashra; Koju, Narayan Prasad (Journal of Advanced Academic Research, 2019)
Conflict between human and wildlife is one of the main threats to the continued survival of many species in different parts of the world, and is also a significant threat to local human populations. As human populations expand and natural habitats shrink, people and animals are increasingly coming into conflict over living space and food. People lose their crops, livestock, property, and sometimes even their lives. Initially, with the use of structured interviews and few key informant survey, 120 households were selected for questionnaire in which 25 were from victim’s family and 95 from Sandhikharka village and the city areas using both purposive and random sampling method. Key informant interviews were also taken with officers of Division forest office and active members of community forest. Similarly, to access the prey diversity, a total of 9 infrared cameras were installed. As the objective of the research, the result was obtained based on secondary and primary data with the use of structured interviews to quantify attitudes based on 5 questions with the given scores where the scores were added together. At the end, the ANOVA test was carried outwit the variances among the control variables influencing the attitude toward leopards while assessing the overall attitudes of people with those scores. The result discusses the mean attitude of illiterate people as negative (-1.03±0.14 SE) towards leopard. Also, overall mean attitude of literate people was negative (-1.19±0.17 SE). Total 6750 images were recorded during study period among them only single event of leopard was captured in the camera trap and 72 independent prey images were captured by infrared camera. Mongoose, Wild cat, Rabbit, Porcupine and barking deer were commonly recorded. Rest of photos recorded were human movement, suggesting less prey abundance and higher human activities in study area.PCA analysis regarding factors affecting leopard human conflict suggested that the distance from water source to local people, distance from toilet to home, land use change going on in the study area, scarcity of water source to wildlife inside the forest, distance to graze livestock are major factors having positive impact on human leopard conflict.